Atividade física e função cognitiva em crianças de Pelotas, RS - Neves, Thais Burlani (2013)
The literature about human cognitive function has demonstrated that physical activity (PA) and aerobic fitness affect brain and cognition during whole life. Studies suggest a positive influence of PA and fitness on human brain structure and function. Research with old people shows that PA promotes brain structure growth, better cognitive performance and memory. Research with adults made up the conclusion that as great as fitness is, better is the cognitive tests performances. Strong evidence about research with children is that related to the practice of PA and cognitive function markers like IQ and academic performance and weak evidence about research with children is related to the mechanisms in which cognitive changes occur like executive function, memory, fats thoughts and attention. Besides that, there are biologic important reasons to hypothesize cognitive benefits generated by PA during childhood. In this period, the central nervous system structures are being developed and the subject becomes vulnerable to stresses due to the enormous brain plasticity and flexibility. Moreover, there are evidences about physical inactivity and lowest levels of aerobic fitness which can causes executive function injuries. The objective of the present project is to verify through a longitudinal study the association between different physical activity intensities and cognitive function in 6 to 13 years old children aiming to contribute with the literature about PA and cognition in preadolescent children